Attitudes of Senior High School Students Towards Career Decision Making - Digamon, Jayson; De La Peña, Jerome (JPAIR Institutional Research, 2021)
Choosing the best career is vital and needs a long process and serious planning for the students to make the right decision. This descriptive study investigated the attitude towards career decision-making of the 302 senior high school students of Gingoog City Comprehensive National High School, Gingoog City, Misamis Oriental. Factors such as sex, grade level, and socioeconomic status were focused on determine their influence on students’ career decisions. The researchers utilized mean, frequency, and percentage, T-test, and F-test/ANOVA, Scheffe Post Hoc Testing, and Multiple Comparisons to organize the data in the study. The results reveal that parents stand as the most prominent factor in students’ career decisions. Likewise, males and females vary in their career choice such that males are more decisive in their career decision-making than females. Further, students who have lower family incomes tend to be more fixed in their career choice than those whose families earn high salaries. It was recommended that school guidance counselors provide counseling for students to be more aware of the possible courses they pursue and the factors that influence them as delineated in this study. Moreover, the parents let their children decide on the courses they desire to pursue in their tertiary education and the profession they carry out in the future.